Prader–Willi syndrome and Tay–Sachs disease in association with mixed maternal uniparental isodisomy and heterodisomy 15 in a girl who also had isochromosome Xq. (6th October 2014) - Zeesman, Susan; McCready, Elizabeth; Sadikovic, Bekim; Nowaczyk, Małgorzata JM
<x xml:space="preserve">Abstract</x> Malsegregation of chromosomes during reproduction can result in uniparental disomy when associated with trisomy rescue, monosomy rescue or gamete complementation. Pathogenicity stemming from uniparental disomy in liveborns results from imprinting disorders or autozygosity for autosomal recessive disorders. We report on a girl with Prader–Willi syndrome and Tay–Sachs disease resulting from maternal uniparental disomy of chromosome 15. The child also had an isochromosome Xq. To further characterize the etiology of the aberrant chromosome 15 and the isochromosome Xq, SNP loci from both chromosomes were assessed in the proband and parents, and genome‐wide DNA methylation analysis was performed. SNP and DNA methylation analysis confirmed maternal uniparental heterodisomy around the Prader–Willi locus, while the region around the HEXA locus showed maternal uniparental isodisomy. This result is consistent with trisomy rescue of a maternal meiosis l error in a chromosome 15 with two meiotic recombinations. SNP analysis of the X chromosomes is consistent with a maternal origin for the isochromosome. © 2014 Wiley Periodicals, Inc.